CHARACTER EDUCATION IN SCHOOL BASED ON LOCAL WISDOM - Suastini, Ni Wayan (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
Education is an essential thing to build national character and culture. Education functions to improve human ability, as mentioned in Law No. 20 of 2003 concerning National Education System Article 3, which states that national education functions develop ability as well as build character and noble national civilization in order to enrich the life of a nation. These abilities include hard skill and soft skill aspects. One of the ways to sharpen the intra-personal and inter-personal abilities is conducting character education at school by considering local wisdom, such as Balinese local wisdom i.e. Tri Hita Karana known as THK. Character education at school which is based on local wisdom of Tri Hita Karana (THK), is a character education which implements character of balanced relationship between the school community and God, balanced relationship among the school community, balanced relationship between school community and entire school facilities environment. Character education at school which is based on local wisdom of THK is expected able to prevent negative effect of global culture intrusion, because THK has become a “taksu” or sociocultural spiritual capital and life philosophy of Balinese. Character education at school which is based on local wisdom of Tri Hita Karana should be developed systematically to improve local excellence of life, national interest, justice, and international competition in world civilization. By implementing local wisdom of THK, school could develop as a center of civilizing competence, becoming basis to develop character and human resources with high work-skill, work culture and strong learning culture, as well as culture of serving people sincerely and reasonably.